2017
DOI: 10.1177/1753465817726314
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is a predictive factor of readmission within 90 days of hospitalization for acute exacerbations of chronic obstructive pulmonary disease: a longitudinal study

Abstract: Background:Readmission after hospital discharge is common in patients with acute exacerbations (AE) of chronic obstructive pulmonary disease (COPD). Although frailty predicts hospital readmission in patients with chronic nonpulmonary diseases, no multidimensional frailty measures have been validated to stratify the risk for patients with COPD.Aim:The aim of this study was to explore multidimensional frailty as a potential risk factor for readmission due to a new exacerbation episode during the 90 days after ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 23 publications
7
58
0
Order By: Relevance
“…Thus, it is only natural that recent past history is a powerful predictor for readmission in this population. Besides this, the next more relevant variable is the Fried aggregate frailty index, which is in agreement with recent literature where frailty has been found to predict hospital readmission and mortality in patients with heart failure (Rampersad et al, ), after Transcatheter Aortic Valve Implantation (Saji et al, ), with chronic obtrusive pulmonary disease (Bernabeu‐Mora et al, ), and in hip and knee arthroplasty (Shin et al, ; Traven et al, ). However, the definition of frailty indices are still a matter of debate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, it is only natural that recent past history is a powerful predictor for readmission in this population. Besides this, the next more relevant variable is the Fried aggregate frailty index, which is in agreement with recent literature where frailty has been found to predict hospital readmission and mortality in patients with heart failure (Rampersad et al, ), after Transcatheter Aortic Valve Implantation (Saji et al, ), with chronic obtrusive pulmonary disease (Bernabeu‐Mora et al, ), and in hip and knee arthroplasty (Shin et al, ; Traven et al, ). However, the definition of frailty indices are still a matter of debate.…”
Section: Discussionsupporting
confidence: 86%
“…Transcatheter Aortic Valve Implantation (Saji et al, 2018), with chronic obtrusive pulmonary disease (Bernabeu-Mora et al, 2017), and in hip and knee arthroplasty (Shin et al, 2016;Traven et al, 2019). However, the definition of frailty indices are still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Echevarría et al, in a validation study of the PEARL index to predict readmission or mortality, proved that by broadening the MRC dyspnoea scale by including a level at which the patient needs help to get dressed or go to the bathroom, the predictive ability of the index improves and that it is better than other multidimensional indexes that only include clinical variables [34]. A similar finding was described in a small Spanish study using the Edmonton Scale of frailty [35]. Other studies have also described poor physical activity as a predictor of readmission [36].…”
Section: Discussionmentioning
confidence: 63%
“…77 Frailty, measured with the Reported Edmonton Frail Scale, predicted the risk of readmission at 90 days in a prospective cohort of patients with acute exacerbation of COPD. 78 It has also been shown that patients with overlap syndrome who are not treated with home continuous positive airway pressure have a greater risk of exacerbation compared with the COPD-only group as mentioned above. 53 Since OSA is still underdiagnosed in COPD patients, particularly in those admitted to the ICU, untreated sleep-disordered breathing could contribute to high readmission rates and their treatment could potentially help to reduce readmissions.…”
Section: Patient-related Risk Factorsmentioning
confidence: 96%